Taking Stock of the Creative Commons Experiment: Monitoring the Use of Creative Commons Licenses and Evaluating Its Implications for the Future of Creative Commons and for Copyright Law - CHELIOTIS, Giorgos (Institutional Knowledge at Singapore Management University, 2007)
We provide an analysis of the use of Creative Commons (CC) licenses, an approach to licens-ing creative works which has become very popular among authors who wish to promote more liberal sharing and use of their work. We provide data demonstrating the popularity of CC, ex-amine which specific license types within the CC framework are most popular, and then iden-tify contributing factors for the relative popularity of some of the license types. This includes in-dividual author incentives, the consistency and aims of the online communities which adopt CC as a licensing model, the underlying medium (text, photography, audio, video or interactive content), the intended use of the work, as well as the sociopolitical, legal and economic back-ground of the jurisdictions where the works are being produced. We show that the spread of the licenses is global and encompasses both developed and developing nations with varied cultural and historical backgrounds, which we claim is indicative of a general social shift to-wards more open collaboration and the rise of a new global consciousness of sharing and par-ticipation across national borders. By examining the relationship between piracy rates and li-cense adoption we find only weak support for the common assumption that a relatively lax or critical view on the part of the population towards intellectual property law is providing fertile ground for licenses like CC which offer a more liberal legal alternative. Only an analysis of the complex legal, economic and geopolitical background of each jurisdiction seems to yield plau-sible explanations for the observed differences in licensing across jurisdictions. In conclusion we examine to what extent copyright law and policy should be informed by the needs and choices of this new generation of authors adopting CC licenses, also taking into consideration the changing interests of society in the digital age.